Correlation of Intraocular Pressure with Central Corneal Thickness in Premature and Full-Term Newborns. Issue 1 (January 2015) - Karahan, Eyyup; Zengin, Mehmet Ozgur; Tuncer, Ibrahim; Zengin, Neslihan
Purpose: To evaluate the relation of central corneal thickness (CCT) and intraocular pressure (IOP) in preterm and full-term newborns. Methods: The study included preterm infants who were admitted to the neonatal intensive care unit. A group of consecutive full-term newborns served as control group. Linear and multiple regression analysis were carried out to assess the association of IOP with sex, gestational/postconceptional age, birthweight, mean oxygenation time, stages of retinopathy of prematurity (ROP), and CCT. Linear and multiple regression analysis were also carried out to assess the association of CCT with sex, gestational/postconceptional age, birthweight, mean oxygenation time, and stages of ROP. Results: Mean IOP was 17.5 ± 2.1 mm Hg in premature newborns and 16.3 ± 1.9 mm Hg in full-term newborns (p = 0.001). Mean CCT was 576.5 ± 16.8 µm in premature newborns and 562.7 ± 18.5 mm in full-term newborns (p = 0.000). Intraocular pressure was not correlated with CCT in preterm infants. Intraocular pressure was moderately correlated with CCT in full-term infants. Sex, postconceptional age at birth and at measurement, age after birth at measurement, birthweight, mean oxygenation time, and stage of ROP were not related to IOP. Central corneal thickness was not correlated with any parameter. Conclusions: Our results showed that the CCT does not affect IOP significantly in preterm infants. More prospective studies are needed for determining the effect of CCT and other ocular and systemic factors on IOP in preterm infants.